RGD-targeted redox responsive nano micelle: co-loading docetaxel and indocyanine green to treat the tumor - Lili Ren; Junfang Nie; Jie Wei; Yaning Li; Jun Yin; Xiaolong Yang; Guoguang Chen (Taylor & Francis Group, 2021)
Cancer, also known as a malignant tumor, has developed into a type of disease with the highest fatality rate, seriously threatening the lives and health of people. Chemotherapy is one of the most important methods for the treatment of cancer. However, chemotherapy drugs have some problems, such as low solubility and lack of targeting, which severely limit their clinical applications. To solve these problems, we designed a block copolymer that has a disulfide bond response. The polymer uses RGD peptide (arginine-glycine-aspartic acid) as the active targeting group, PEG (polyethylene glycol) as the hydrophilic end, and PCL (polycaprolactone) as the hydrophobic end. Then we utilized the amphiphilic polymer as a carrier to simultaneously deliver DOC (docetaxel) and ICG (indocyanine green), to realize the combined application of chemotherapy and photothermal therapy. The antitumor efficacy in vivo and histology analysis showed that the DOC/ICG-loaded micelle exhibited higher antitumor activity. The drug delivery system improved the solubility of DOC and the stability of ICG, realized NIR-guided photothermal therapy, and achieved an ideal therapeutic effect.